Policy Strategies for Accelerating Poverty Reduction In Central Maluku Regency: Evidence from Program Convergence and Innovation - Ushan, Yuyun Masriana; Bugis, Muhammad; Matitaputty, Izaac Tonny (LP2M IAIN Palopo, 2026)
Poverty is a multidimensional development challenge that requires integrated and sustainable policy responses. Central Maluku Regency has introduced several innovative poverty alleviation programs, namely Masohi Merakyat, Dompet Siafa, and MANTAB (Pinjaman Tanpa Bunga, Interest-Free Loans), as locally driven initiatives to address poverty. This study aims to assess the effectiveness of these innovative programs and to formulate policy strategies for accelerating poverty reduction in Central Maluku Regency. This study employed a descriptive approach that combines qualitative and quantitative methods. The findings indicate that, while the implementation of the innovation programs can be classified as effective, their overall level of effectiveness remains relatively modest, with several indicators falling within the moderately effective category. Key constraints identified include limitations in the accuracy of poverty data, insufficient program socialization, suboptimal cross-sectoral synergy, and weaknesses in monitoring and evaluation mechanisms. Based on a SWOT analysis, this study recommends an aggressive strategy focused on strengthening program convergence, improving data quality, optimizing stakeholder collaboration, and enhancing adaptive monitoring and evaluation systems that are responsive to local conditions.